Choosing between Alternative Structural Equations Estimated by Instrumental Variables - Giles, David E. A.; Low, Chan Kee (The Review of Economics and Statistics, 1981)
of economic time series similar to the observed high frequency series. A transformation that converts these series to serially uncorrelated stationary time series would therefore introduce the same conversion to the residuals. Although the discussion in this paper has been limited to the problem of distribution, a similar treatment can be given to the problem of interpolation and extrapolation by related series. As has been shown in the paper of Chow-Lin, the three problems can be treated simultaneously by properly defining the transformation matrix B.